Tinjauan Hukum Islam Terhadap Larangan Menikah Pada Bulan Kapit (Studi Kasus di Desa Trusmi Wetan Kecamatan Plered Kabupaten Cirebon) - Daya, Aan; Shodiqin, Akhmad; Nursyamsudin, Nursyamsudin (TAQNIN: Jurnal Syariah dan Hukum, 2025)
Based on marriage data from the Office of Religious Affairs (KUA) in Plered District for the period of Dzulqa’dah 2023 to Dzulqa’dah 2024, there were no recorded marriages in Trusmi Wetan Village during the month of Kapit. This qualitative study applies a case study method with data collected through in-depth interviews and field observations. The aim is to explore the factors behind the community's adherence to the prohibition of marriage in the month of Kapit, the perspectives of religious leaders, and the Islamic legal analysis of this tradition. The findings show that the community continues to uphold this belief due to strong adherence to ancestral customs and the influence of generational teachings. Religious leaders in the village express two differing views: some uphold the tradition as part of local wisdom, while others argue there is no Islamic legal basis for such a restriction. From an Islamic legal perspective, the prohibition falls under the category of ‘urf fasid (invalid custom), as it contradicts Islamic teachings that do not impose time-based restrictions on marriage. The study highlights the need for educational efforts that align Islamic law with local cultural practices.Keywords: Wedding, Kapit Month, 'Urf